Human-Centered Design for Collaborative Innovation in Knowledge-based Economies - Silva, Tiago Filipe Pereira (2021)
This research explores a university-industry collaboration based on the case study of an innovation project based on Stanford University's ME310 Design Innovation program. The Porto Design Factory and IKEA Industry joined forces to tackle a problem using what has come to be called a human-centered design approach. The case study provides an understanding of outcomes that reveal the potential of using a human-centered design approach to solve technical problems while enhancing customer experience. It also identifies the benefits that each institution gained by collaborating. The outcomes show that companies benefit from building interfaces with external partners, and that universities are relevant players in the innovation ecosystem, satisfying their third mission of being entrepreneurial institutions.